Bilinear Time-Frequency Analysis Techniques for Power Quality Signals - Abdullah, Abdul Rahim; Sha'ameri, Ahmad Zuri; Mohd Said, Nurul Ain; Mohd Saad, Norhashimah; Jidin, Auzani (2012)
Bilinear time-frequency distributions (TFDs) are powerful techniques that offer good time and frequency resolution of time-frequency representation (TFR). It is very appropriate to analyze power quality signals which consist of non-stationary and multi-frequency components. However, the TFDs suffer from interference because of cross-terms. This paper presents the analysis of power quality signals using bilinear TFDs. The chosen TFDs are smooth-windowed Wigner-Ville distribution (SWWVD), Choi-Williams distribution (CWD), B-distribution (BD) and modified Bdistribution (MBD). The power quality signals focused are swell, sag, interruption, harmonic, interharmonic and transient based on IEEE Std. 1159-2009. To identify and verify the TFDs that operated at optimal kernel parameters, a set of performance measures are defined and used to compare the TFRs. The performance measures are main-lobe width (MLW), peak-to-side lobe ratio (PSLR), signal-to-cross-terms ratio (SCR) and absolute percentage error (APE). The result shows that SWWVD is the best bilinear TFD and appropriate for power quality signal analysis.